Evaluation and management of pediatric hypertensive crises: hypertensive urgency and hypertensive emergencies - Patel, Nirali H (Open Access Emerg Med, 2012)
Hypertension (HTN) in the pediatric population is estimated to have a world-wide prevalence of 2%–5%. As with adults, pediatric patients with HTN can present with hypertensive crises include hypertensive urgency and hypertensive emergencies. However, pediatric blood pressure problems have a greater chance of being from secondary causes of HTN, as opposed to primary HTN, than in adults. Thorough evaluation of a child with a hypertensive emergency includes accurate blood pressure readings, complete and focused symptom history, and appropriate past medical, surgical, and family history. Physical exam should include height, weight, four-limb blood pressures, a general overall examination and especially detailed cardiovascular and neurological examinations, including fundoscopic examination. Initial work-up should typically include electrocardiography, chest X-ray, serum chemistries, complete blood count, and urinalysis. Initial management of hypertensive emergencies generally includes the use of intravenous or oral antihypertensive medications, as well as appropriate, typically outpatient, follow-up. Emergency department goals for hypertensive crises are to (1) safely lower blood pressure, and (2) treat/minimize acute end organ damage, while (3) identifying underlying etiology. Intravenous antihypertensive medications are the treatment modality of choice for hypertensive emergencies with the goal of reducing systolic blood pressure by 25% of the original value over an 8-hour period.